Mengenal gaya belajar murid dan tantangan bagi guru untung lebih adapatif - muhammad, haidar haidar (Maliki Interdisciplinary Journal, 2025)
Each student has a different way of understanding lessons, some find it easier to grasp information through images, some prefer to listen to explanations, and some learn more effectively when actively moving. These differences in learning styles are a challenge for teachers in delivering material fairly and meaningfully. This article discusses the importance of recognizing the variety of student learning styles such as visual, auditory, kinesthetic, and mixed learning styles. Teachers are faced with heterogeneous classes, limited time, and minimal training to adjust teaching methods to student needs. However, with an adaptive approach such as conducting initial assessments, implementing differentiated learning, and using media and technology, teachers can create a more inclusive and enjoyable learning process. More than just delivering material, the role of teachers is now to be learning facilitators who understand the unique way each student learns. This article is expected to be a reflection and practical guide for educators to be better prepared to face the dynamics of increasingly diverse classrooms.